Use of Glosses for Reading with Computers by Turkish Pre-Service English Language Teachers - Umut M. Saliho?lu (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The purpose of the study is to investigate the dictionary and glossary use of pre-service English language teachers while reading on the computer. The participants of the study were 26 first- and second-year pre-service English language teachers at a large Turkish public university. In order to explore their clicking and gloss-use behavior while reading, a web page with a pop-up glossary window was designed, and a screen capture tool was used to record the participants' actions. The findings of the study suggested that pre-service teachers were usually careful about their selection when they were looking up a word with. However, the results showed a discrepancy between the words that were claimed to be known and the words that were actually checked when reading with glossed texts. The study also confirmed learners' tendency for more look-ups with pop-up glosses mentioned in the literature.